Can urethral re-bulking improve the outcomes of a prior urethral bulking?. (January 2022) - Giammò, Alessandro; Ammirati, Enrico; Geretto, Paolo; Manassero, Alberto; Squintone, Luisella; Falcone, Marco; Del Popolo, Giulio; Pistolesi, Donatella; Risi, Oreste; Costantini, Elisabetta; Giannantoni, Antonella; Mancini, Vito; et al.
Aims: To analyze the outcomes of urethral re-bulking in the treatment of female stress urinary incontinence. Materials and Methods: We performed a multicenter observational retrospective study, which included all consecutive patients treated with urethral re-bulking for the treatment of persistent stress or mixed urinary incontinence after a previous urethral bulking. Objective outcomes were evaluated with the 24 h pad-test, while PGI-I questionnaires were administered to evaluate subjective outcomes. Clinical outcomes were assessed before re-bulking procedure and at last follow-up. Mann–Whitney's U test was used for subgroup analysis. Shapiro-Wilk's tests were used as normality tests. Results: In total, 62 patients who underwent urethral re-bulking between 2013 and 2020 in a multicenter setting were included. Most patients did not reach complete continence after the first procedure (n = 56) while the remainder reported recurrence of urinary incontinence after initial benefit. Median age at surgery was 66 (IQR: 55-73). Median overall follow-up was 30 months (IQR: 24-41). Median time occurred between the first procedure and reintervention was 12 months (IQR: 7-27). Bulking agents for the re-bulking procedures were bulkamid(n = 56), macroplastique(n = 4), and Prolastic(n = 2). A statistically significant reduction of median 24 h pad test from 100 g(IQR: 40-200) to 35 g(IQR: 0-120) was observed (p = 0.003). Dry rate after rebulking was 36.6%, while 85.4% patients declared themselves 'very much improved' or 'much improved' (PGI-I 1-2). Very few low-grade complications were observed (n = 4). A single case of major complication occurred. Conclusions: Urethral re-bulking can be an effective technique for the treatment of stress urinary incontinence refractory to a previous urethral bulking and can determine a cumulative benefit after the first procedure.